You are on page 1of 5

LECTURE 12

Integrating Factors

Recall that a differential equation of the form (12.1) M (x,y) + N (x,y)y = 0 is said to be exact if (12.2) and that in such a case, we could always find an implicit solution of the form (12.3) ψ(x,y) = C with ∂ψ = M (x,y) ∂x (12.4) ∂ψ = N (x,y) . ∂y Even if (12.1) is not exact, it is sometimes possible multiply it by another function of x and/or y to obtain an equivalent equation which is exact. That is, one can sometimes find a function µ(x,y) such that is exact. Such a function µ(x,y) is called an ntegrating factor. If an integrating factor can be found, then the original differential equation (12.1) can be solved by simply constructing a solution to the equivalent exact differential equation (12.5). (12.5)

∂M = ∂N , ∂y ∂x

µ(x,y)M (x,y) + µ(x,y)N (x,y)y = 0

Example 12.1. Consider the differential equation

x y +x
2 3

1+y

2

This equation is not exact; for (12.6) and so
∂M ∂y ∂N ∂x

dy = 0 . dx
= 3x = 1+y
2 2

= =

∂ ∂x

∂ ∂y

x

xy
2

1+y

3

2

.

∂M = ∂N . ∂y ∂x xy
3

However, if we multiply both sides of the differential equation by µ(x,y) = 1 we get

which is not only exact, it is also separable. The general solution is thus obtained by calculating
1

y dy = 0 x+ 1+ y dx
2 3

8) µ = µ ( x) .12) dx This is a first order linear differential equation for µ hat we can solve! According to the formula developed in Section 2. The formula (12.1.y) + N (x.e. i.11) as N ∂y ∂y N ∂y ∂x . in general.y)) = ∂x (µ(x)N (x.12) is (12. Carrying out the differentiations (using the product rule.13) µ(x) = A exp −p(x)dx = A exp 1 ∂M − ∂N dx . INTEGRATING FACTORS 2 H ( x) 1 H2 (y) = = 2 xdx = 1 2x 1+ y 2 1 y 3 dy = 2y 2 + ln |y| and then demanding that or y is related to x by H1 (x) + H2 (y) = C 1 2 x − 2 2y2 1 + ln |y| = C . ∂ ∂ (12. Now. then dy (12.y) dx must be exact. In certain cases. then necessarily dµ dx depends only on x. 0.7) M (x.11) requires the right hand side of (12.y)) .7) so long as 1 ∂M − ∂N depends only on x.11) to be a function of x alone. (12.y) + µ(x)N (x.y) dx We shall suppose that there exists an integrating factor for this equation that depends only on x: (12. and the fact that µ(x) depends only on x). it is rather easy to find an integrating factor.8) and (12.13) thus gives us an integrating factor for (12.9) µ(x)M (x. the general solution of (12. Equations with Integrating Factors that depend only on x.10) ∂y (µ(x)M (x.12. (12. we get or (12. y) for a given differential equation is very difficult. the problem of finding an integrating factor µ(x.11) dµ = 1 ∂M − ∂N µ . the selfconsistency of equations (12. We presume this to be the case and set p(x) = − 1 ∂M − ∂N dµ + p(x)µ = 0 . Consider a general first order differential equation dy = 0 .1. N ∂y ∂x dµ N + µ ∂N µ ∂M = ∂y dx ∂x Thus. dx N ∂y ∂x Now if µ is depends only on x (and not on y).. so that we can rewrite (12. If µ is to really be an integrating factor.

18) requires the right hand side of (12.y)y = 0 ∂M ∂y (12. dµ + p(y)µ = 0 . M ∂x ∂y (12.19) is µ(y) = A exp −p(y)dx = A exp 1 ∂N − ∂M dx (12. then dy µ(y)M (x.1.y) dx (12.3.15) µ = µ( y ) . Equations with Integrating Factors that depend only on ..y)) .22) depends only on x then (12.y) + N (x.18) dy M ∂x ∂y Now since µ is depends only on y (and not on x). F 1 = N − ∂N ∂x µ(x) = exp F (x)dx 1 .y)) = ∂x (µ(y)N (x. we get ∂ ∂ ∂y (µ(y)M (x.15) and (12. Thus. INTEGRATING FACTORS 3 first order differential equation 0.2.21) is not exact. If 0.14) M (x. Summary: Finding Integrating Factors.19) According to the formula developed in Section 2. (12.21). the selfconsistency of equations (12. and the fact that µ(y) depends only on y). then necessarily dµ dy depends only on y . Suppose that M (x.e.17) (12.23) will be an integrating factor for (12.14) so long as 1 ∂N − ∂M depends only on y.y) + N (x.20) The formula (12. A. dy M ∂x ∂y . y Consider again the general dy = 0 .y) + µ(y)N (x.y) dx We shall suppose that there exists an integrating factor for this equation that depends only on y: (12. the general solution of (12.11) as (12. Carrying out the differentiations (using the product rule.16) must be exact. dµ M + µ ∂M = µ ∂N dy ∂y ∂x or dµ = 1 ∂N − ∂M µ . We presume this to be the case and set 1 ∂N − ∂M p(y ) = − M ∂x ∂y so that we can rewrite (12. If µ is to really be an integrating factor. (12.11) to be a function of y alone. i.12.20) thus gives us an integrating factor for (12.

27) ∂ψ = e x (x + y ) .y)(x + y )dy = 0 3 F ≡ 1 ∂M ∂y ∂N ∂x F ≡ 2 2 2 1 M − − ∂N ∂x ∂M ∂y = Since F depends on both x and y. 3 2 2 3 2 2 3 3 2 3 2 2 2 2 3 3 1 3 1 3 3 3 3 3 1 2 1 2 3 2 3 3 . F 2 = ∂N ∂x M − ∂M ∂y µ(y) = exp F (y)dy 2 C. must be exact. we can consistently construct an integrating factor that is a function of x alone. 3 Since +2 +3 2 =2 = x y this equation is not exact. (12. by construction. then there is little hope of constructing an integrating factor. We seek to find a function is exact.23) we get µ(x) = exp F1 (x)dx N x y − 2x = 3(x + y ) = 3 x +y x +y −3 x + y 2x − 3x − 2x − 3y = = 3x y + 2xy + y 3x y + 2xy + y 3 2 +2 +3 2 2 2 2 2 2 2 2 2 2 2 x 2 3 2 3 = exp 3dx = e x .27) must be of the form ψ(x.26) Here (3 2 + 2 x y xy + y )dx + (x + y )dy = 0 3 2 2 M (x. y) = x ye x + y e x + h (y) ψ(x. INTEGRATING FACTORS 4 B.y)(3x y + 2xy + y )dx + µ(x.21). Now x ∂N ∂x 2 2 µ such that µ(x. However.12. Comparing these expressions for ψ (x. Applying formula (12. y) = e x x y + e x y + C . a constant. Example 12.y) N (x.2. So we seek a function ψ such that ∂ψ = e x (3x y + 2xy + y ) ∂x (12. If (12.y) ∂M = 3x ∂y 2 2 = = 3 2 +2 2+ 2 x y xy + y x y . y) = x ye x + y e x + h (x) . 3 We can now employ this µ(x) as an integrating factor to construct a general solution of e x (3x + 2x + 3y ) + e x (x + y )y = 0 which. y) we see that we msut take h (y) = h (x) = C .25) will be an integrating factor for (12. Thus. we cannot construct an integrating factor depending only on y from F . function ψ satisfying (12. If neither A nor B is true. since F does not depend on y. ∂y Integrating the first equation with respect to x and the second equation with respect to y yeilds ψ(x.24) depends only on y then (12.

the general solution of (12.12. INTEGRATING FACTORS 5 Therefore. 3 2 3 3 .20) is found by solving e xx y + e xy = C for y.